Interplay Between the Human Resource Development Activities and Organizational Commitment - Ovesni, Kristinka; Nataša Matović; Ivana Luković (European Journal of Multidisciplinary Studies, 2017)
This mixed methods research was aimed to explore relationship between the human resource development activities and the commitment of employees. In the research, we applied explanatory sequential design using nested samples for the quantitative and qualitative components of the study to foster deeper understandings of these relationships. In the quantitative component, data were obtained with scales, and analyzed from 609 employees in different companies in Serbia, while for qualitative component semi-structured interviews were conducted with 29 respondents from the same sample. The collected data were subjected (in the first component) to a few common (frequencies, std. deviation, means, etc.) and more complex statistical proceedings (canonical correlation analysis), and in the second component were subjected to the qualitative content analysis. The quantitative results indicate complex interaction of affective, continuance, and normative components of organizational commitment with different human resource development activities, while the qualitative data revealed deeper meaning of these connections.
Keywords: human resource development, human resource development activities, organizational commitment, mixed methods